Mechanism of Borane‐Catalyzed Oligomerization of Arylallenes and Arylacetylenes - Qu, Zheng‐Wang; Zhu, Hui; Grimme, Stefan (European journal of organic chemistry, 2024)
Recently, it was shown that Piers’ borane [HB(C6F5)2]2 can induce rapid oligomerization reactions of arylacetylenes and arylallenes. Using phenylallene PhCH=C=CH2 and phenylacetylene PhCCH as typical substrates, the detailed mechanisms of borane‐induced oligomerization are disclosed by extensive state‐of‐the‐art DFT calculations. Following initial regioselective hydroboration of unsaturated C=C or C≡C bonds, further oligomerization and structural rearrangement reactions may occur through unique boryl‐enabled conversions such as 1,3‐boryl‐shift, allylboration, 1,2‐carboboration, and 1,5‐electrocyclization. Together with stepwise transborylation with hydroboranes such as pinacolborane HBpin, such fundamental reactions may pave a catalytic way to borane‐induced oligomerization of arylacetylenes and arylallenes. Detailed mechanisms of Piers’ borane‐induced oligomerization of unsaturated arylallene and arylacetylene through unique boryl‐enabled steps including hydroboration, 1,3‐boryl‐shift, allylboration, carboboration, 1,5‐electrocyclization, and multistep rearrangement, followed by catalytic turnover through transborylation with stable pinacolborane are disclosed by extensive dispersion‐corrected DFT calculations, paving the avenue to boryl‐enabled catalytic synthesis.